The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/17476933.2016.1198787
|View full text |Cite
|
Sign up to set email alerts
|

Elliptic Problems in with Critical and Singular Discontinuous Nonlinearities

Abstract: Let Ω be a bounded domain in R N , N ≥ 3 with smooth boundary, a > 0, λ > 0 and 0 < δ < 3 be real numbers. Define 2 * := 2N N − 2 and the characteristic function of a set A by χA. We consider the following critical problem with singular and discontinuous nonlinearity:We study the existence and the global multiplicity of solutions to the above problem.1991 Mathematics Subject Classification. 35J20, 35J60.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Using similar ideas as in (ZA) case, it can be shown that v is a weak solution of (P λ ). Then the rest of the proof follows exactly same as Lemma 3.3 of [9] or Lemma 2.7 of [13]. Proof of Theorem 1.3: The proof follows directly from Proposition 5.1 (Appendix) and Theorem 1.2 of [1].…”
Section: Multiplicity Resultsmentioning
confidence: 93%
“…Using similar ideas as in (ZA) case, it can be shown that v is a weak solution of (P λ ). Then the rest of the proof follows exactly same as Lemma 3.3 of [9] or Lemma 2.7 of [13]. Proof of Theorem 1.3: The proof follows directly from Proposition 5.1 (Appendix) and Theorem 1.2 of [1].…”
Section: Multiplicity Resultsmentioning
confidence: 93%
“…A similar problem with the Laplacian operator in R 2 was studied by Saoudi and Kratou in [35]. In [16] Dhanya, Prashanth, Sreenadh and Tiwari considered the singular case with critical exponential growth and discontinous nonlinearity. The inhomogeneous singular Neumann case was studied in [36].…”
Section: Introductionmentioning
confidence: 97%
“…But the nonlinearities have polynomial growth. 2) In [16], [20], [35] and [36] were studied the singular case with a nonlinearities with exponential growth. However, here we study problems with a general operator which brings some technical difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…If a = λ and b = 1, and q ∈ (0, 1), authors proved a global multiplicity result. While in [3,14], researchers improvised the results of [26] and proved the global multiplicity result for q ∈ (0, 3). In [28], Hirano, Saccon, and Shioji studied the problem (1.1) with a = λ and b = 1, and q ∈ (0, 1).…”
Section: Introductionmentioning
confidence: 99%